Fundamental concepts in the design of experiments - Hicks, Charles R (Oxford Univ. Press, 1999)
These problems are selected to emphasize the basic philosophy of design. Another purpose is to present a logical sequence of designs that fit into a consistent outline, for every type of experiment, the distinctions among the experiment, the design, and the analyses are emphasized. Since this theme of experiment design analysis is to be highlighted throughout the text, the first chapter presents and explains this theme. the second chapter reviews statistical inference, and the remaining chapters follow a general outline, with an experiment - design- analysis summary at the end of each chapater.